Kryzys rodziców dziecka z niepełnosprawnością w perspektywie nowych narzędzi normalizacyjnych - Doroszuk, Joanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Social and cultural transformations determine the functioning of a disabled child’s family. The Internet, support groups or associations are the new normalisation tools parents can use. They can affect both the structure of his or her parenting as well as the process of coping in difficult situations. The author analyses the social and emotional situation of parents of children with disabilities, based on her research. They describe the significant categories and areas important for further scientific exploration.